Odpowiedzi

Najlepsza Odpowiedź!
2010-02-17T20:10:05+01:00
4(2x-5) dla x=-2
a) 4*(2*(-2) -5) = 4* (-4-5) = 4* (-9) = -36

-9(5x+7) dla x=-1
b) -9*(5*(-1) +7)= -9*2 = -18

x²+3x-16 dla x=9
c) 9²+3*9 -16= 81+27-16= 92

5x -⅓(x+10) dla x=-40
d) 5*(-40) -⅓(-40+10)= -200 -⅓(-30)= -200 +10 = -190
2010-02-17T20:12:14+01:00
Hmm.. podstawić za x to trudno? ;D
a) 4(2x-5) dla x=-2
4*2*(-2) - 20 = -36
b) -9(5x+7) dla x=-1
-9*5*(-1) +(-9)*7 = -18
c)x²+3x-16 dla x=9
9^2 + 3 *9 - 16 = 92
d) 5x -⅓(x+10) dla x=-40
5*(-40) - 1/3 * (-40) + 1/3 * 10 = -183 i 1/3